Seminario sobre Planificacion Participativa por objetivos del Programa de Frijol de Bolivia (1990, Santa Cruz, Bolivia). Informe (International Center for Tropical Agriculture, 1990)
The report of the seminar conducted in Santa Cruz de la Sierra (Bolivia), to discuss the applicability of the goal-oriented participating planning method to bean cultivation in the country, is presented. Bean production at the national level is analyzed; its importance lies in its nutritive value, in the possibility of its use in crop association or rotation, and in the generation of income for small farmers. The scope, beneficiaries, and executors of the Programa de Frijol para la Zona Andina (PROFRIZA) are indicated and the groups relevant for the program characterized, specifying their interests and resources. The main limitations for bean cultivation in the country are analyzed, which include insufficient research on the crop, lack of knowledge on agronomic management, low consumption of the product, lack of established marketing channels, and lack of coordination of crop-related activities. The program proposes to increase bean production and productivity in Bolivia by means of crop dissemination, use of more productive var. and of integrated control methods for the main pests and diseases, production and use of good quality seed, technology generation and transfer with the participation of farmers, improvement of the agronomic management of the crop, better access to credit, creation of an interinstitutional coordination organism, and conducting market and promotion studies. Different actions to be taken to meet the proposed goals are indicated. (CIAT)